2009
DOI: 10.3171/2008.10.spi08333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperglycemia on progressive paraparesis in a rat metastatic spinal tumor model

Abstract: Object Hyperglycemia has been shown to potentiate ischemic injury of the spinal cord by quenching vasodilators and potentiating tissue acidosis and free radical production. Steroid-induced hyperglycemia is a common event in the surgical management of metastatic epidural spinal cord compression (MESCC). The goal in this study was to determine whether experimentally induced hyperglycemia accelerates neurological decline in an established animal model of MESCC. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…In a rat spinal tumor model, hyperglycemia shortened the time to paralysis; in addition, a lower epidural tumor volume was required to cause paralysis in hyperglycemic rats. 26 Human studies examining the association between hyperglycemia and outcomes after spinal injuries are mainly limited to retrospective analyses. One review from a registry at a level 1 trauma center in Australia found hyperglycemia (at the time of injury) to be associated with subsequent functional disability and suboptimal physical health status in patients with spine injuries.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat spinal tumor model, hyperglycemia shortened the time to paralysis; in addition, a lower epidural tumor volume was required to cause paralysis in hyperglycemic rats. 26 Human studies examining the association between hyperglycemia and outcomes after spinal injuries are mainly limited to retrospective analyses. One review from a registry at a level 1 trauma center in Australia found hyperglycemia (at the time of injury) to be associated with subsequent functional disability and suboptimal physical health status in patients with spine injuries.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%
“…[18][19][20][21][22][23] Experimental data in animals suggest that hyperglycemia may play a deleterious role in the setting of spinal cord ischemic injury; however, prospective human studies are lacking. [24][25][26] The purpose of this study was to examine the association between lower extremity weakness (LEW) and the glucose levels of blood and cerebrospinal fluid (CSF) in patients undergoing multibranched endovascular aneurysm repair (MBEVAR) of pararenal aortic aneurysms (PRAAs) and TAAAs.…”
mentioning
confidence: 99%
“…30 This model has been previously used to test numerous treatment modalities ranging from local chemotherapy to radiotherapy. 2,3,13,14,31 In the context of the current study, this model tests the safety of applying local hyperthermia to tumors abutting the highly sensitive neural tissues of the spine and great vessels.…”
Section: Discussionmentioning
confidence: 99%
“…31 Anesthetized rats were placed on sterile drapes, and the abdomen was shaved and disinfected with a povidone-iodine solution. A 3-cm midline incision centered between the iliac crests was made to the skin, following the procedure described by Mantha et al 30 to expose the underlying abdominal muscles.…”
Section: Tumor Implantationmentioning
confidence: 99%
“…19,20,29,35,37 One group studying cerebral ischemia in rats found that hyperglycemia reduced cerebral plasma volume, cerebral blood flow, and blood-brain barrier transport. 20 Another study investigating the effects of glucose levels following traumatic brain injury found that acute but not delayed hyperglycemia increased the contusion area and elevated neutrophil accumulation in the area of the cortical contusion.…”
Section: Discussionmentioning
confidence: 99%